(untitled) (Journal of Laboratory Animal Science, 2021)
Technical azadirachtin, a major component of neem, has low acute/subchronic toxicity and non-mutagenic/teratogenic in mammalian species along with minimal disruption to the ecosystem. The present in vitro study aims to address the potential evaluation of azadirachtin-A, a tetranortritarpinoid of neem seed kernel, on the antioxidant system of rat spermatozoa to promote oxidative stress in a dose-dependent manner. To assess the effect of the azadirachtin-A on activities of superoxide dismutase (SOD), catalase, Glutathione reductase (GR), Glutathione peroxidase (GPx), α-Glucosidase, production of Hydrogen peroxide (H2O2) and level of lipid peroxidation (LPO) in rat spermatozoa, increasing quantities 0.5 mM, 1 mM, 1.5 mM and 2.0 mM per ml of the azadirachtin-A was added to the cultured medium prior to the addition of cauda epididymal spermatozoa. The spermatozoa were observed at 6th h post-culture and the expressions of enzyme activities and production of H2O2, level of LPO were recorded. The activities of antioxidant enzymes decreased significantly while the levels of H2O2 generation and LPO increased significantly in azadirachtin-A treated spermatozoa in a dose dependent manner when expressed in terms of milligram protein and milligram DNA. The activity of α- glucosidase, a negative control against antioxidant enzymes, did not show any significant change at any of the doses. The results suggest that graded doses of azadirachtin-A elicits depletion of antioxidant defense system in sperm, indicating azadirachtin-A induced oxidative stress in the epididymal sperm of rats.